2019
DOI: 10.1101/561548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internal noise measures in coarse and fine motion direction discrimination tasks, and the correlation with autism traits

Abstract: People with autism spectrum disorder (ASD) display abnormalities in motion processing. Motion perception abnormalities in ASD have been linked to high levels of internal noise (unreliable neuronal fluctuations), and deficits in motion pooling (integrating local motion into a global percept). However, the literature overall is equivocal. Traditionally, internal noise in ASD has been investigated through additive internal noise, comparing ASD and control groups. To date, multiplicative internal noise has not bee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…The degree to which an individual exhibits autistic traits can be measured using the Autism-spectrum Quotient (AQ), introduced by Baron-Cohen et al (2001), or the Social Responsiveness Scale (SRS-2) (Constantino and Gruber, 2012). Vilidaite et al (2017) showed, using a psychophysical double-pass paradigm, that the amount of internal noise was positively correlated with the degree to which participants exhibited autistic traits on the AQ [see also (Orchard et al, 2021)].…”
mentioning
confidence: 99%
“…The degree to which an individual exhibits autistic traits can be measured using the Autism-spectrum Quotient (AQ), introduced by Baron-Cohen et al (2001), or the Social Responsiveness Scale (SRS-2) (Constantino and Gruber, 2012). Vilidaite et al (2017) showed, using a psychophysical double-pass paradigm, that the amount of internal noise was positively correlated with the degree to which participants exhibited autistic traits on the AQ [see also (Orchard et al, 2021)].…”
mentioning
confidence: 99%